The Time is Now for Disruptive Innovation in Pre-Exposure Prophylaxis Adherence Monitoring - Giffin Daughtridge; Elijah Kahn-Woods; Casper Enghuus; Shane Hebel (HIV/AIDS Research and Treatment-Open Journal, 2020)
Monitoring adherence to pre-exposure prophylaxis is a critical component of reaching ending the human immunodeficiency virus infection (HIV) epidemic goals in the US. Currently, providers still depend on “self-report” pre-exposure prophylaxis (PrEP) adherence, whereby providers ask their patients about their recent pill taking habits. There appears to be growing consensus across the HIV prevention community that “self-report” is an inadequate method of identifying that is in-need of additional adherence support services. In a recent survey, 97% of providers report utilizing self-reported adherence because it is convenient, but only 10% of these providers believe it is accurate. While “self-report” is convenient, evidence and testimonials from diverse stakeholders across the HIV prevention landscape indicate that there is a desire for more accurate, effective adherence monitoring methods. In this mini-review, we will briefly synthesize the emerging evidence and propose a solution to ensure all patients receive the support needed to protect them from HIV acquisition.